Applied video analysis for coaches: Weightlifting examples - Garhammer, J.; Newton, H. (International Journal of Sports Science and Coaching, 2013)
The following article presents a reasonably detailed introduction to video analysis, as can be used by coaches in many sports for both qualitative (subjective) and quantitative (objective) evaluation of their athletes from a two dimensional (2D) point of view. Video cameras and their set-up to capture video records of training or competition performances of athletes are emphasized, along with a review of five video analysis software programs, two of which can be obtained free of charge. Examples from the sport of Weightlifting are provided, but similar applications can be made to other sports. A brief general history of cimematographic (film) and video analyis is given, in addition to a history that is more specific to Weightlifting.